The impact of brazilian clusters on local development: a propensity score matching approach - Alderete, María Verónica (2020)
The theme of the article is the impact of Brazilian clusters on local development: a propensity score matching approach. The objective is to determine if there are improvements on the local development of municipalities with clusters compared to those without clusters. At the same time, the objective is to provide the explanatory factors of clustering in a territory. The methodology is Propensity Score Matching technique (ROSEMBAUM; ROBIN, 1983). The object of study are the non-metropolitan municipalities of the São Paulo State, in Brazil. Data is collected from the SEADE Foundation and the United Nations Program for the years 2009 and 2010. The results obtained show statically significant differences in the average local development (measured by well-known indexes) between municipalities with and without clusters. Municipalities with clusters achieve a higher local development than municipalities without clusters. The present paper contributes to the scant quantitative research on the impact of clusters on local development.